2021
DOI: 10.5194/acp-21-9779-2021
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric and stratospheric wildfire smoke profiling with lidar: mass, surface area, CCN, and INP retrieval

Abstract: Abstract. We present retrievals of tropospheric and stratospheric height profiles of particle mass, volume, surface area, and number concentrations in the case of wildfire smoke layers as well as estimates of smoke-related cloud condensation nuclei (CCN) and ice-nucleating particle (INP) concentrations from backscatter lidar measurements on the ground and in space. Conversion factors used to convert the optical measurements into microphysical properties play a central role in the data analysis, in addition to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 129 publications
4
87
0
Order By: Relevance
“…The retrieval of aerosol microphysical properties such as particle volume, mass, and surface area concentration and estimates of cloud-relevant properties such as CCNC and INPC is performed by means of the POLIPHON (Polarization Lidar Photometer Networking) approach Ansmann, 2016, 2017;Marinou et al, 2019;Ansmann et al, 2019Ansmann et al, , 2021. Lidar input data sets are the height profiles of the 532 nm backscatter coefficient and the PLDR.…”
Section: Lidar Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrieval of aerosol microphysical properties such as particle volume, mass, and surface area concentration and estimates of cloud-relevant properties such as CCNC and INPC is performed by means of the POLIPHON (Polarization Lidar Photometer Networking) approach Ansmann, 2016, 2017;Marinou et al, 2019;Ansmann et al, 2019Ansmann et al, , 2021. Lidar input data sets are the height profiles of the 532 nm backscatter coefficient and the PLDR.…”
Section: Lidar Productsmentioning
confidence: 99%
“…6a) were on the order of 10 Mm −1 in October, around 4-5 Mm −1 during the main winter months, and mostly ≤ 3 Mm −1 at the end of the lifetime of the smoke layer. From the measured layer mean extinction coefficients, mass concentrations of the smoke particles were derived (Ansmann et al, 2021) and ranged from 0.4-2 µg m −3 during the autumn and winter months. Note that AOT values for a clean stratosphere are around 0.001-0.002 (Sakai et al, 2016;Baars et al, 2019), and minimum extinction coefficients are of the order of 0.1-0.2 Mm −1 .…”
Section: Wildfire Smoke Layer In the Utls Regimementioning
confidence: 99%
“…where δ m (= 0.004 for our lidar system) is the molecular depolarization ratio that is related to the specification of the narrowband filters in the receiving unit of the lidar system (Behrendt and Nakamura, 2002). The relative uncertainty for δ p is generally on the order of 5 %-10 % (Mamouri et al, 2013).…”
Section: Polarization Lidarmentioning
confidence: 99%
“…Otherwise, the Klett-Fernald method (Fernald, 1984;Klett, 1981) is applied using the elastic signals to retrieve the backscatter coefficients. The relative uncertainties are in the range of 5 %-10 % for backscatter coefficients and depolarization ratios at 355 and 532 nm (Ansmann et al, 1992;Baars et al, 2012). The backscatter coefficient retrieval at 1064 nm may be possible with a relative uncertainty of 15 % using only an elastic signal by assuming a proper lidar ratio.…”
Section: Polly Xt Lidarmentioning
confidence: 99%
“…Adam et al (2020) present a methodology for analyzing the biomass burning events recorded in the EARLINET database and provide a literature review of lidar-derived intensive parameters of biomass burning aerosols (46 reference values from 39 cited papers), including fresh and aged ones. Lidar observations showed that biomass burning aerosols are medium-to highly absorbing particles with an almost spherical shape and small particle size, producing medium to high lidar ratios, low depolarization ratios, and high Ångström exponents (Alados-Arboledas et al, 2011;Amiridis et al, 2009;Baars et al, 2012;Müller et al, 2007;Murayama et al, 2004;Nepomuceno Pereira et al, 2014).…”
mentioning
confidence: 99%